ANALISIS USIA IDEAL PERKAWINAN DALAM PERSPEKTIF MAQASID SYARI’AH - Teguh Anshori (Fakultas Syariah IAIN Ponorogo, 2019)
AbstractThis study departs from a juridical confusion regarding the age limit of marriage with other provisions regarding age. Article 7 Paragraph 1 of Law No. 1 of 1974 concerning Marriage, states that marriage is only permitted if the male has reached the age of 19 (nineteen) years and the female has reached the age of 16 (sixteen) years. Law Number 23 the Year 2002 concerning Child Protection states that what is called a 'child' is a person who is under 18 years of age. As for Law Number 26 of 2000 concerning the Human Rights Court, it is explained that an adult category is a person who is 18 years old. The Marriage Age Maturing Program (PUP) offers a solution, namely the ideal age of marriage seen from various perspectives is a minimum of 20 years for women and 25 years for men. Departing from this, this study seeks to explore why the need for an ideal marriage age limit according to Maqasid Sharia, as well as how to analyze Maqasid Sharia against the provisions of the ideal age limit of marriage in Mating the Age of Marriage (PUP). To answer this question, this study uses Maqasid Sharia theory with the basic assumptions of the theory, namely the protection of religion, soul, reason, descent, and property. The normative-empirical approach in this study refers to the study of the formal aspects of the Marriage Age Maturity (PUP) program.This study found that the existence of an ideal marriage age limit in Maqasid Sharia theory can have a variety of positive impacts when applied. The positive impact is in the form of increasing the ideal age of marriage; increasing family welfare; improved education; increased understanding related to the importance of the ideal age of marriage; and parents increasingly understand the importance of the ideal age of marriage when they want to marry their children. The provisions of the ideal marriage limit in Maturing Marriage Age (PUP) are at least 20 years for women and 25 years for men. Sharia Maqasid's analysis results in this study indicate that the ideal age provisions applied in the Marriage Age Maturing (PUP) program are the right solution in creating a good Sharia Maqasid family. The application of these provisions can regulate relations between men and women; look after offspring; creating sakinah, mawaddah, warahmah families; maintain lineage; maintain diversity in the family; set the pattern of good relationships in the family and regulate financial aspects in the family.Keywords: Maqasid Sharia, Maturity Maturity (PUP). AbstrakPenelitian ini berangkat dari sebuah kerancuan yuridis mengenai batas usia perkawinan dengan ketentuan lain mengenai usia. Pasal 7 Ayat 1 UU Nomor 1 Tahun 1974 tentang Perkawinan, menyebutkan bahwa perkawinan hanya diizinkan apabila pihak laki-laki telah mencapai umur 19 (sembilan belas) tahun dan pihak perempuan sudah mencapai usia 16 (enam belas) tahun. Undang-Undang Nomor 23 Tahun 2002 tentang Perlindungan Anak menyebutkan bahwa yang disebut dengan ‘anak’ adalah orang yang masih berusia di bawah 18 tahun. Adapun dalam Undang-Undang Nomor 26 Tahun 2000 tentang Pengadilan Hak Asasi Manusia, dijelaskan bahwa kategori dewasa adalah orang yang berumur 18 tahun. Program Pendewasaan Usia Perkawinan (PUP) menawarkan solusi, yaitu usia ideal perkawinan dilihat dari berbagai perspektif adalah minimal 20 tahun bagi perempuan dan 25 tahun bagi laki-laki. Berangkat dari hal tersebut, penelitian ini berusaha menelusuri mengapa perlunya batas usia ideal perkawinan menurut Maqasid Syariah, serta bagaimana analisis Maqasid Syariah terhadap ketentuan batas usia ideal perkawinan dalam Pendewasaan Usia Perkawinan (PUP). Untuk menjawab pertanyaan tersebut, penelitian ini menggunakan teori Maqasid Syariah dengan asumsi dasar teori yaitu perlindungan terhadap agama, jiwa, akal, keturunan, dan harta. Pendekatan normatif-empiris dalam penelitian ini mengacu pada kajian aspek formal program Pendewasaan Usia Perkawinan (PUP).Penelitian ini menemukan bahwa adanya batas usia ideal perkawinan dalam teori Maqasid Syariah dapat memberikan berbagai dampak positif apabila diterapkan. Dampak positif tersebut berupa meningkatnya usia ideal perkawinan; meningkatnya keluarga sejahtera; meningkatnya pendidikan; meningkatnya pemahaman terkait pentingnya usia ideal perkawinan; serta orang tua semakin memahami pentingnya usia ideal perkawinan ketika hendak menikahkan anaknya. Adapun ketentuan batas ideal perkawinan dalam Pendewasaan Usia Perkawinan (PUP) yaitu minimal 20 tahun bagi perempuan dan 25 tahun bagi laki-laki. Hasil analisis Maqasid Syariah dalam penelitian ini menunjukkan bahwa ketentuan usia ideal yang diterapkan dalam program Pendewasaan Usia Perkawinan (PUP) merupakan solusi tepat dalam menciptakan Maqasid Syariah keluarga yang baik. Penerapan ketentuan tersebut mampu mengatur hubungan antara laki-laki dan perempuan; menjaga keturunan; menciptakan keluarga sakinah, mawaddah, warahmah; menjaga garis keturunan; menjaga keberagamaan dalam keluarga; mengatur pola hubungan yang baik dalam keluarga dan mengatur aspek finansial dalam keluarga.